Kualitas Udara Ambien Parameter Sulfur Dioksida (SO2) pada Rona Lingkungan Awal Pembangunan Jalan Alternatif Matabondu – Lalingato: (Studi Kasus Desa Matabondu – Lalingato, Kabupaten Kolaka Timur, Provinsi Sulawesi Tenggara) - Masere, Muh. Agung; Sumarlin, Sumarlin; Assiddieq, Moch (Universitas Muhammadiyah Kendari, 2024)
Through Indonesian Goverment Regulation Number 22 of 2021 explains that the implementation of environmental protection and management, which is meant by air pollution incidents, is the entry or introduction of substances, energy and other components into the ambient air by human activities, so that the air quality drops to a certain level which causes the ambient air unable to fulfill its function.” Decreased quality of ambient air because pollution in ambient air has exceeded a certain threshold, thereby endangering living things and the environment. Taking samples of Sulfur Dioxide (SO2) gas using an impinger, laboratory testing results of sulfur dioxide (SO2) samples at four environmental baselines for alternative road construction Matabondu - Lalingato obtained SO2 level results, the first point was 16.80 µg/m3, the second point was 18.50 µg/m3, the third point was 18.50 µg/m3, and the fourth point was 14.90 µg/m3 at the four research locations. The SO2 level is the first point 16.80 µg/m3, the second point 18.50 µg/m3, the third point 18.50 µg/m3, and the fourth point 14.90 µg/m3. So it can be concluded that sulfur dioxide (SO2) pollution is still below the quality standard limit set by the Government of the Republic of Indonesia Regulation Number 22 of 2021 on Implementation of Environmental Protection and Management.